Different responses in Mandarin cultivars uncover a role of cuticular waxes in the resistance to citrus canker - Favaro, María Alejandra (2020)
'Okitsu' is a mandarin cultivar showing substantial resistance to X. citri subsp. citri (X. citri). We have previously shown that this cultivar has significantly lower canker incidence and severity than 'Clemenules', particularly during early stages of leaf development in the field. This differential response is only seen when the leaves are inoculated by spraying, suggesting that leaf surface contributes to resistance. In this work, we have studied structural and chemical properties of leaf surface barriers of both cultivars. Ultrastructural analysis showed a thicker cuticle covering epidermal surface and guard cells in young 'Okitsu' leaves than in 'Clemenules'. This thicker cuticle was associated with a smaller stomatal aperture and reduced cuticle permeability. These findings correlated with an accumulation of cuticular wax components, including primary alcohols, alkanes, and fatty acids. None of these differences were observed in mature leaves, where both cultivars are equally resistant to the bacterium. Remarkably, mechanical alteration of cuticular thickness of young 'Okitsu' leaves allows canker development. Furthermore, cuticular waxes extracted from young 'Okitsu' leaves have higher antibacterial activity against X. citri than 'Clemenules'. Taken together, these data suggest that a faster development of epicuticular waxes in 'Okitsu' leaves play a central role in its resistance to X. citri.